Performance of Islamic and Conventional Banks in Pakistan: A Comparative Study - Aziz, Shahab; Husin, Maizaitulaidawati; Hashmi, Shujahat Haider (International Journal of Economics and Financial Issues, 2016)
This study is conducted to find out financial performance of Islamic and conventional banks operating in Pakistan for the year 2006-2014. For comparison purpose five Islamic and five similar sized conventional banks have been selected. The comparison has been made on average values of different ratios of both Islamic and conventional banks. The comparison shows that Islamic banks performance has been better in terms of efficiency, return and asset quality. However Islamic banks are struggling in terms of advances, investment, liquidity, deposits and capital as conventional banks performance is better in these areas. Islamic banks are charging higher spread and share of distributable income to depositors is far less as compared to conventional banks. Islamic banks need to focus on fair distribution of profit to its depositors in order to increase its credibility and help in achieving overall Islamic socio economic objectives of justice and equality. Islamic banks should focus on new products development and innovative solutions to meet client's needs, also Islamic banks needs to strengthen their equity base. Keywords: Financial Performance, Financial Ratios, Comparison, Islamic banks, Conventional Banks JEL Classifications: E44, G21